Niewydolność serca - definicja, klasyfikacja, epidemiologia, objawy i leczenie = Heart failure - definition, classification, epidemiology, symptoms and treatment - Beata Kowalczyk; Rafał Czyż; Bożena Kaźmierska (Kazimierz Wielki University, 2017)
Kowalczyk Beata, Czyż Rafał, Kaźmierska Bożena. Niewydolność serca - definicja, klasyfikacja, epidemiologia, objawy i leczenie = Heart failure - definition, classification, epidemiology, symptoms and treatment. Journal of Education, Health and Sport. 2016;6(11):352-367. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.168089 http://ojs.ukw.edu.pl/index.php/johs/article/view/4008       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 23.11.2016.       Niewydolność serca - definicja, klasyfikacja, epidemiologia, objawy i leczenie Heart failure - definition, classification, epidemiology, symptoms and treatment   Beata Kowalczyk1, Rafał Czyż2, Bożena Kaźmierska1   1 - Uniwersytet Medyczny im. Piastów Śląskich we Wrocławiu 2 - Katedra Medycyny Ratunkowej Uniwersytetu Medycznego we Wrocławiu,     Streszczenie   W ciągu ostatnich 50 lat pojawiło się wiele określeń niewydolności serca. Dokonał się również znaczący postęp w postrzeganiu i leczeniu tej choroby. Skuteczność leczenia i rehabilitacji przekłada się na redukcję klasy NYHA i poprawę frakcji wyrzutowej lewej komory serca. Istotnie poprawiło się rokowanie chorych z umiarkowaną i ciężką postacią niewydolności. Kluczem do wczesnego rozpoznania niewydolności serca są jej objawy przedmiotowe i podmiotowe. Niestety pomimo ogromnego rozwoju medycyny niewydolność serca jest nadal poważnym problemem klinicznym, społecznym i ekonomicznym. Liczba zachorowań stale rośnie. W kompleksowej opiece nad pacjentem z niewydolnością serca oprócz leczenia farmakologicznego znaczącą rolę odgrywa odpowiednie przygotowanie chorego do życia z niewydolnością serca. Celem artykułu jest podsumowanie zagadnień definicji, klasyfikacji, epidemiologii, objawów i leczenia niewydolności serca.   Słowa kluczowe: niewydolność serca, definicja, klasyfikacja, epidemiologia, leczenie.     Abstract   In the last 50 years there have been many definitions of heart failure. It has been made significant progress in the perception and treatment of the disease. The effectiveness of treatment and rehabilitation translates into a reduction in NYHA class and improve the ejection fraction of the left ventricle. Significantly improved the prognosis in patients with moderate or severe heart failure. The key to early diagnosis of heart failure are its signs and symptoms. Heart failure unfortunately continues despite the enormous development of medicine is serious clinical, social and economic problem. The number of cases continues to grow. In the comprehensive care of patients with heart failure in addition to pharmacological treatment plays an important role adequate preparation of the patient to live with heart failure. Objectives of this article is a summary of issues of definition, classification, epidemiology, symptoms and treatment of heart failure.   Key words: heart failure, definition, classification, epidemiology, treatment.